Morphological differences between playing positions in elite male handball players - Vrbik, I.; Cizmek, A.; Gruic, I. (Croatian Sports Medicine Journal, 2011)
This study presents morphological characteristics of 37 elite Croatian junior and senior national male handball players. A set of 27 anthropometric measures were carried out on 9 wing attack players, 6 pivots, 5 goalkeepers and 17 back court players. The body fat percentage and the BMI were calculated. ANOVA showed statistically significant differences between wing attackers and other playing positions in variables of body height, body mass, biltareral measures of leg and arm length, abdomen skinfold, circumference of right extended upperarm, circumference of right flexed upperarm, bilateral measures of forearm circumference, circumference of right upperleg, bilateral measures of lower leg circumference and abdominal circumference. Morphological characteristics can influence the ability of players to respond better to the requirements of the certain position in the game